Salix transect of Europe: additional leaf beetle (Chrysomelidae) records and insights from chrysomelid DNA barcoding - Canty, Roy (Biodivers Data J, 2019)
Abstract. Occurrence patterns of chrysomelid beetles (Coleoptera: Chrysomelidae), associated with willow (Salix spp.) at 42 sites across Europe, have previously been described. The sites form a transect from Greece (lat. 38.8 °N) to arctic Norway (lat. 69.7 °N). This paper reports additional records and the results of DNA sequencing in certain genera. Examination of further collections from the transect has added 13 species in the genera Aphthona, Chrysomela, Cryptocephalus, Epitrix, Galerucella (2 spp.), Gonioctena, Phyllotreta (2 spp.), Pachybrachis (3 spp.) and Syneta. We also report the sequencing of the DNA regions cytochrome oxidase 1 (CO1) and cytochrome B (cytB) for a number of samples in the genera Plagiodera, Chrysomela, Gonioctena, Phratora, Galerucella and Crepidodera. The cytB sequences are the first available for some of these taxa. The DNA barcoding largely confirmed previous identifications but allowed a small number of re-assignments between related species. Most notably, however, it was evident that the southernmost material (Greece and Bulgaria) of specimens, previously treated as Crepidodera aurata sens. lat., belonged to a distinctive molecular cluster. Morphological re-examination revealed these to be C. nigricoxis Allard, 1878. This is an example of how morphotaxonomy and DNA barcoding can work iteratively to refine identification. Our sequences for C. nigricoxis appear to be the first available for this taxon. Finally, there is little geographic structure evident, even in widely dispersed species.